Analisis Faktor Eksternal dan Internal dalam Strategi Bisnis PT Sedana Proteksi Sinergi Pialang Reasuransi: Analysis of External and Internal Factors ESG Integration in Business Strategy at PT Sedana Proteksi Sinergi Pialang Reasuransi - Marah Kerma Mardame Manurung (OGZ Research & Publishing, 2025)
Abstract This study analyzes the integration of Environmental, Social, and Governance (ESG) into the strategy of PT Sedana Proteksi Sinergi (Sedana Re), an Indonesian reinsurance broker, using PESTEL, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and SWOT/IE Matrix. Results show IFE 2.50 (internal conditions average/threshold), EFE 2.55 (opportunities slightly dominate), and PESTEL 3.90 (supportive context). The IE Matrix positions the firm at cell 5 (hold & maintain), implying targeted internal consolidation (WO)—finalizing the ESG roadmap, strengthening human capital and IT, and data governance—alongside pilot ESG monetization (SO). Findings affirm ESG as a nucleus for strategic renewal rather than mere compliance for mid-scale reinsurance brokers. Keywords: ESG; reinsurance broker; PESTEL; IFE; EFE; SWOT; IE Matrix; turnaround strategy